Bone mineral density assessment according to Italian essential assistance levels: a positive predictive value analysis based on administrative data - Abate, Veronica; Vergatti, Anita; Cavati, Guido; Magelli, Simone; Varriale, Alfonso; Merlotti, Daniela; De Filippo, Gianpaolo; Piccinocchi, Gaetano; D’Elia, Lanfranco; Gennari, Luigi; Rendina, Domenico (Frontiers in Endocrinology, 2025)
BackgroundOsteoporosis (OP) is the gradual loss of bone mineral density (BMD), predisposing to fragility fractures. It can be the result of aging or menopause in primary OP or other diseases and medications in secondary OP. The gold standard diagnostic tool for low BMD is represented by dual-energy X-ray absorptiometry (DXA), which has been included among the Essential Assistance Levels (EALs) in Italy for adequate prescription. This observational study based on administrative data evaluates whether the EALs are designed to predict OP (designed to include OP screening), with subsequent BMD-DXA evaluation in Italian men and women. The SIMON database was used to select women and men scheduled to undergo BMD-DXA according to EALs.ResultsBMD was evaluated in 18,087 subjects [Male (M): Female (F) 889: 17198; mean age 71.3 ± 9.3 years; body mass index (BMI): 26.9 ± 4.5 Kg/m2] for primary OP and in 6,503 subjects (M: F 649: 5854; mean age 70.5 ± 9.4 years; BMI: 25.4 ± 4.8 Kg/m2) for secondary OP, both suspected on the basis of EALs. Primary OP was confirmed by DXA in 13,759 (80.0%; mean age 71.9 ± 9.2 years; BMI: 26.5 ± 4.8 Kg/m2) women and in 551 men (62.0%; mean age 69.3 ± 9.4 years; BMI: 26.5 ± 4.8 Kg/m2). Secondary OP was confirmed by DXA in 4,683 women (80.0%; mean age 70.7 ± 8.9 years; BMI: 25.3 ± 5.0 Kg/m2) and in 514 men (79.2%; mean age 69.7 ± 9.4 years; BMI: 26.3 ± 5.3 Kg/m2). The positive predictive values of EALs for OP were higher among women for primary OP than men and similar in both genders without any significant difference in secondary OP.ConclusionItalian EAL are a useful diagnostic tool for primary of OP in both sexes, with significant gender dimorphism evident in secondary OP.